Fikih maqasid syariah: teori dan praktik - Al-Ayubi, Solahuddin; Ismail, Nurizal (Rajawali Pers, 2025)
This book offers a deep understanding of Maqasid al-Shariah—the higher objectives of Islamic law that underpin every aspect of a Muslim’s life, including acts of worship (ibadah), social and financial transactions (muamalah), and philanthropy. With a holistic approach,